1994
DOI: 10.3109/01913129409016297
|View full text |Cite
|
Sign up to set email alerts
|

Parachordoma

Abstract: Parachordoma is a soft tissue tumor that has a light microscopic appearance similar to that of chordoma, and the immunostaining properties of the two tumors are alike. The clinical findings and light microscopy of one case of parachordoma are presented together with ultrastructural observations on this tumor and parachordomas from five additional patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The term parachordoma was coined by Dabska 26 years later, 2 when she described in detail the features of 10 cases (including the five cases reported by Laskowski). Since this time less than 40 cases have been reported, about half of which have included details of immunohistochemistry 2–23 . The reported tumors have been nearly twice as common in men than women and the ages of those affected ranged from 4 to 86 years (mean, 32 years).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The term parachordoma was coined by Dabska 26 years later, 2 when she described in detail the features of 10 cases (including the five cases reported by Laskowski). Since this time less than 40 cases have been reported, about half of which have included details of immunohistochemistry 2–23 . The reported tumors have been nearly twice as common in men than women and the ages of those affected ranged from 4 to 86 years (mean, 32 years).…”
Section: Discussionmentioning
confidence: 99%
“…Early reports suggested that parachordoma was related to axial chordoma and that it might arise from aberrantly located notochordal rests, 12 but a number of recent studies have highlighted immunohistochemical, ultrastructual and cytogenetic differences between the two tumors 3,7 , 15,25 . On the basis of the results of these studies it has been proposed that parachordoma is distinct from chordoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parachordoma is an uncommon soft‐tissue tumor; approximately 40 cases have been reported to date 1–23 . It was first described by Laskowski in 1951 as ‘chordoma periphericum’ considering its histological resemblance to chordoma, with a suggestion that it might be derived from specialized synovial cells 1 .…”
mentioning
confidence: 99%
“…However, histogenesis of parachordoma has remained uncertain. Ectopic notochordial remnants (chordoma), lipoblasts, chondroblasts, and many others such as a possible affiliation with synovial tumors including synovial sarcoma, have been claimed 3–6 . More recently, a myoepithelial cell origin has been propounded 24–27 .…”
mentioning
confidence: 99%